Reliance of coastal intertidal food webs on river input – Current and future perspectives. (June 2019) - Vinagre, Catarina; Madeira, Carolina; Dias, Marta; Narciso, Luís; Mendonça, Vanessa
Graphical abstract: Highlights: Isotopic analysis was conducted in intertidal waters near a major river. Reliance on benthic affinity prey was high for top consumers. Top consumers rely heavily on POM as a carbon source. Intertidal food webs near a major river depend on terrestrial inputs. Droughts should disrupt the detrital energy pathway that feeds coastal waters. Abstract: Climate change models predict an important decrease in precipitation in some parts of the world, which will lead to a decrease in river plume magnitude. River plumes can have an important enhancing effect on coastal secondary production and sustain important fisheries. Studies using stable isotopes have been proven successful in characterizing the energy pathways that sustain coastal fisheries and their dependence on terrestrial matter inputs. This has been shown in subtidal coastal waters affected by major rivers, but not in the adjacent intertidal food webs. Since intertidal food webs function as nursery and refuge areas for important commercial species it is important to understand if they too are dependent on river carbon inputs. In this study, carbon and nitrogen isotopes were used to investigate the incorporation of terrestrial particulate organic matter (POM) input into the intertidal communities of the northern and southern coast adjacent to the river Tagus. In total 34 food web components were analysed. Among the top consumers, 16 fish species and two shrimp species were identified. Nine commercial fish species were analysed. Reliance on benthic affinity prey was high for most top consumers. Top consumers relied heavily on POM as a carbon source. Intertidal food webs near the Tagus river mouth are dependent on terrestrial inputs. The increase in droughts predicted by climate change models should impact these coastal food webs, since the benthic energy pathway upon which this food web relies, should be negatively impacted.